The Perception Customers about the Means Quality Infrastructure of Ngantang Public Health Center - Dwi Ratna; Sandu Siyoto; Byba Melda Suhita (Journal for Quality in Public Health, 2020)
Background: Ngantang Public Health Center, being a public health center, always tries to apply minimum service standards. Services provided are a form of effort organized to meet community needs. Purpose: The research objective was to explore customer perceptions about the quality of buildings, equipment, human resources at Public Health Center Ngantang. Methodhs: The design used in this research is a qualitative descriptive study with a case study design, which describes customer perceptions about infrastructure; quality of buildings, equipment, human resources at the Public Health Center Ngantang. The sampling technique of this research is purposive sampling technique. The informants in this study consisted of 21 people, namely 5 BPJS PBI, 5 General, 5 Independent BPJS and 6 patient companions as triangulation informants. Data collection techniques using observation, interviews and documentation. Results: The results of the research on customer perceptions about the Public Health Center Ngantang building are the contours of lands prone to landslides, adequate parking facilities, unsafe security facilities, building components and materials are good enough, facilities for persons with disabilities and the elderly are incomplete, consumables are not yet available, furniture is less structured, human resources or labor lack of sympathy and empathy. Conclusion: By conducting this research, it can be used as a reference for Public Health Center Ngantang in improving the quality of infrastructure. consumables are not yet available, water furniture is less structured, human resources or labor lack sympathy and empathy. By conducting this research, it can be used as a reference for Public Health Center Ngantang in improving the quality of infrastructure.